Edukasi Seksualitas/Reproduksi Anak Penyandang Disabilitas pada Pegawai Panti Sosial Menuju Profesionalitas Pelayanan : Sexuality/Reproductive Education for Children with Disabilities in Social Care Facilities Towards Professional Services - Dwi Novrianda; Hermalinda; Deswita (NERS Jurnal Keperawatan, 2016)
Social Institution Bina Grahita Harapan Ibu (PSBGHI) is the only social institution in West Sumatra Province who provide social services and rehabilitation for people with mental disabilities. Persons with disabilities who are in the shelter are from various districts / cities in West Sumatra which amounted to 100 people. This orphanage is located in Kalumbuk, Padang City with an area of 5,007 m2. Since the implementation of regional autonomy, PSBGHI employees totaling 44 people either civil servants and honorarium received minimally training, seminars, even a refresher material. Partners in this IbM classified into 2 groups: 1) group of civil power as many as 24 people, with educational background is not a disability, and 2) a group of honorary staff of 20 people. Problems formulated partners namely the lack of knowledge about reproduction and sexuality in the development of persons with disabilities, reproductive problems / sexuality of persons with disabilities, and to tackle the problem. Results showed an increase understanding of sexuality and handling of sexuality problems encountered in children with disabilities. Therefore, the provision of material and playback video in the form of seminar is one alternative that can be given.